Schizophrenia and visual backward masking: a general deficit of target enhancement - Herzog, Michael H.; Roinishvili, Maya; Chkonia, Eka; Brand, Andreas (Frontiers in Psychology, 2013)
The obvious symptoms of schizophrenia are of cognitive and psychopathological nature. However, schizophrenia affects also visual processing which becomes particularly evident when stimuli are presented for short durations and are followed by a masking stimulus. Visual deficits are of great interest because they might be related to the genetic variations underlying the disease (endophenotype concept). Visual masking deficits are usually attributed to specific dysfunctions of the visual system such as a hypo- or hyper-active magnocellular system. Here, we propose that visual deficits are a manifestation of a general deficit related to the enhancement of weak neural signals as occurring in all other sorts of information processing. We summarize previous findings with the shine-through masking paradigm where a shortly presented vernier target is followed by a masking grating. The mask deteriorates visual processing of schizophrenic patients by almost an order of magnitude compared to healthy controls. We propose that these deficits are caused by dysfunctions of attention and the cholinergic system leading to weak neural activity corresponding to the vernier. High density electrophysiological recordings (EEG) show that indeed neural activity is strongly reduced in schizophrenic patients which we attribute to the lack of vernier enhancement. When only the masking grating is presented, EEG responses are roughly comparable between patients and control. Our hypothesis is supported by findings relating visual masking to genetic deviants of the nicotinic 7 receptor (CHRNA7).